2020
DOI: 10.3390/su12093524
|View full text |Cite
|
Sign up to set email alerts
|

The Multiplier Effects of Food Relocalization: A Systematic Review

Abstract: Background: The purchase of local food is often argued to stimulate local economies through multiplier effects; this argument is questioned in this paper. Methods: The ScienceDirect, Wiley Online Library, Taylor and Francis Online, SpringerLink, AgECON, and Emerald databases were searched systematically. A complementary search in Google Scholar was also carried out. Peer-reviewed studies published between 2000 and 2019 were identified using multiple search terms. Data about four types of multipliers (output, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 76 publications
1
10
0
Order By: Relevance
“…Benedek et al [30] examined the possible multiplier effects of local products in the local economy. The results show that employment-and income multipliers can be considered more evident, but outputand value-added multipliers were more situation-dependent.…”
Section: The Role Of Short Supply Chains In Rural Developmentmentioning
confidence: 99%
“…Benedek et al [30] examined the possible multiplier effects of local products in the local economy. The results show that employment-and income multipliers can be considered more evident, but outputand value-added multipliers were more situation-dependent.…”
Section: The Role Of Short Supply Chains In Rural Developmentmentioning
confidence: 99%
“…Similar results were presented in the empirical study of Mundler and Laughrea ( 2016 ), which found mainly positive (farmers’ welfare, local development, welfare of the community and environmental protection) or neutral effects (economic role of SFSC in local economy, the access to fresh and healthy food). The socio-economic benefits and shortcomings for the producers were, for example, studied by Schmutz et al ( 2017 ), Opitz et al ( 2019 ) Benedek et al ( 2020 ) and Malak-Rawlikowska ( 2019 ). The latter study reveals a slight preference for SFSC (in general) and against long chains according to the better prices, and regular and assured payments (economic stability), but also certain shortcomings of specific SFSC types, such as pick-your-own and internet sales, due to small quantities and the occasional character of these purchases.…”
Section: Discussionmentioning
confidence: 99%
“…Another difficulty in this research field results from the limited access to qualitative and quantitative data of the benefits of SFSC (Mundler and Laughrea 2016 ) and a lack of baseline and longitudinal data (Kneafsey et al 2013 ). Concerning the impacts of the agri-food sector and especially of local food systems (including SFSCs), it becomes obvious that the relevance and sufficiency of impacts were sometimes overestimated and possible counter-effects or trade-offs were neglected (Michel-Villarreal et al 2019 ; Benedek et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, as in the case of global world economic phenomena, it is not possible to speak about only the positive aspects of localization. The complexity of the issue is discussed by Benedek et al (2020) [12] with regard to the food industry and by Németh et al (2020) [13] concerning locally produced energy. European and global businesses are increasingly moving towards sustainable value chains.…”
Section: The Role Of Global and Local Trends In World Economic Processesmentioning
confidence: 99%